أثر إدارة السلوك التنظيمي على جودة تقديم الخدمات التعليمية بالتطبيق علي جامعة الفرات الأهلية –اجدابيا دولة ليبيا (Comprehensive Journal of Science, 2025)
The study addressed the impact of organization behavior management on the  a quantity of education service provided. Applet to Al-furat private university. The study problem ubs represented in a main question. What are the impacts of organizational behavior management on the quality of educational services provided to Al-Furat private university? The study aimed to determine. The eytont of the impact of organizational behavior. On the quantity of educational service’s provided to all – Furat private university  . then apply the disruptive and analytical approach and the questionnaire. The study concluded with a number of results, the most imp Orland of which are: the demographic data chow a the largest age  group is the group ranging from 30 to40 years and that the most comman academic degree
Keywords: organizational behavior, quality of service provision, Al-Furat University, Ajdabiya city.